The effects of behavioural parent training program on families of children with attention-deficit/hyperactivity disorder - Zadeh, Majid Darvishi; Baba, Maznah; Mokhtar, Halimatun Halaliah; Wan Jaafar, Wan Marzuki; Momtaz, Yadollah Abolfathi (Marsland Press, 2011)
The present study evaluated the effectiveness of Behavioural Parent Training Program (BPTP) on families of children with ADHD. Using quasi- experimental design, sixty parents of ADHD children from an ADHD centre for children with behavioural and emotional disorders were randomly assigned to experimental and control groups. The program developed by Barkley was administered in nine 90-minutes sessions in nine weeks with a one-month follow-up session. Conners’ Parent Rating Scales-Revised and ADHD Rating Scale-IV were employed to measure treatment outcomes. Since data did not meet the assumptions of normality distribution, a series of nonparametric tests using SPSS version-16 were used in the statistical analyses. The results of Friedman Tests showed significant results for all the subscales. Further investigation of the results using Wilcoxon Signed Rank Test also showed a statistically significant reduction in symptoms of ADHD and related problem (Optional behaviour, Cognitive problems/inattention and ADHD Index). The results imply that BPTP can be effective for reducing symptoms of ADHD. The outcome of the study could benefit family counselors, psychologists and specifically for psycho-educational interventions as a single treatment. Theoretical and practical implications of the findings, avenues for future research and limitations of the study are discussed.